INDIGENOUS PEOPLES OF THE BRITISH DOMINIONS AND THE FIRST WORLD WAR/ Timothy C. Winegard - Warden, Herman (Scientia Militaria - South African Journal of Military Studies, 2013)
Timothy Winegard saw active duty in the Canadian Reserve Force from 2001 to 2010 and served on detachment duty to the British Army for a two-year period. He obtained various academic degrees from 1999 onwards, among others a BA Hons degree in History and an MA in War Studies. The book under discussion here is the third work by this author. Other publications from this author include Oka: A convergence of cultures and the Canadian forces (2008), For King and Kanata (2011), and the latest work entitled Indigenous peoples of the British dominions and the First World War (2012).